2017
DOI: 10.15406/jdvar.2017.06.00179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Non-Specific Immune Stimulant (Amplimune™) on the Health and Production of Light Feedlot Calves

Abstract: An increasing concern from both producers and consumers regarding the overuse and misuse of antibiotics leading to the development of antibiotic-resistant pathogens dictates the need for new research objectives. These new objectives should be directed towards exploring different management practices and the use of antibiotic alternative products to treat or prevent disease in cattle and other food producing animals. The main objective of this pilot study was to determine if a bovine immunotherapeutic (Amplimun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There has been controversy on whether inactivated vaccines maintain their innate training effects, mainly because evidence from human clinical data has claimed that the beneficial non-specific effects would be limited to live vaccines 63 , as seen by comparison of BCG and gamma-irradiated BCG 64 . On the other hand, there is proof that a vaccine composed of cell wall components from Mycobacterium phlei in oil-emulsion was able to decrease overall mortality in feedlot cattle 65 , and also to improve survival after enterotoxigenic E. coli challenge in neonatal cattle 66 . In any case, we believe that this training effect in inactivated vaccines should be revised since we have demonstrated cross protective effects of heterologous inactivated vaccines against PTB in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy on whether inactivated vaccines maintain their innate training effects, mainly because evidence from human clinical data has claimed that the beneficial non-specific effects would be limited to live vaccines 63 , as seen by comparison of BCG and gamma-irradiated BCG 64 . On the other hand, there is proof that a vaccine composed of cell wall components from Mycobacterium phlei in oil-emulsion was able to decrease overall mortality in feedlot cattle 65 , and also to improve survival after enterotoxigenic E. coli challenge in neonatal cattle 66 . In any case, we believe that this training effect in inactivated vaccines should be revised since we have demonstrated cross protective effects of heterologous inactivated vaccines against PTB in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…E.g., mice pre-treated with FCA had markedly reduced viremia following inoculation with Foot-and-mouth disease virus (10). Recently, a commercial veterinary vaccine containing cell wall components from M. phlei in oil-emulsion was reported to decrease all-cause morbidity in feedlot cattle (11), and to improve survival after Enterotoxigenic Escherichia coli induced diarrhea in neonatal cattle (12). Early murine experimental studies of non-specific effects also found that heat-killed BCG or M. fortuitum administered s.c. or i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Amplimune ® is an immune stimulant based on the cell-wall fractions of M. phlei, a naturally occurring non-pathogenic mycobacterium (Filion et al 1999), emulsified in squalane and phosphate buffered solution (PBS). It is commercially available in the USA, Canada and New Zealand (Nosky et al 2017). In these jurisdictions, it is used for the primary objective of preventing and treating an assortment of livestock diseases via augmentation of non-specific activity of the innate immune system (Griebel 1999;Nosky et al 2017).…”
Section: Open Accessmentioning
confidence: 99%
“…It is commercially available in the USA, Canada and New Zealand (Nosky et al 2017). In these jurisdictions, it is used for the primary objective of preventing and treating an assortment of livestock diseases via augmentation of non-specific activity of the innate immune system (Griebel 1999;Nosky et al 2017). For example, the health and clinical signs in dairy calves suffering from enterotoxigenic Escherichia coli infection were significantly improved when calves were administered Amplimune (Romanowski et al 2017).…”
Section: Open Accessmentioning
confidence: 99%